Benefits of Mindfulness for Parenting in Mothers of Preschoolers in Chile - Corthorn, Carolina (Frontiers in Psychology, 2018)
The present study evaluated whether mothers’ participation in a mindfulness-based intervention led to statistically significant differences in their general levels of stress, depression, anxiety, parental stress, mindful parenting, and mindfulness. Forty-three mothers of preschool-age children participated, 21 in the intervention group and 22 in the comparison group. Scores of mental health variables were within normal ranges before the intervention. All of the participants worked at the Universidad Católica de Chile (Catholic University of Chile), and their children attended university preschool centers. Repeated measured ANOVA analysis were performed considering differences between gain scores of each group, rather than post-treatment group differences. This was chosen in order to approach initial differences in some of the measures (mindfulness, mindful parenting, and stress) probably due to self-selection. As predicted, the intervention group showed a significant reduction in general and parental stress and an increase in mindful parenting and general mindfulness variables when compared with the comparison group. Effect sizes ranged from small to medium, with the highest Cohen’s d in stress (general and parental) and mindful parenting. In most cases, the significant change was observed between pre- and post-test measures. Follow-up measures indicated that the effects were maintained after 2 months.